Conflict of Interest in the Utilization of the Micro-Hydro Power Plant in Karangtengah Village, Banyumas Regency - Taufan Bintang Sejati; Dimas Purbo Pambudi; Titi Rahmawati (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the conflict of interest in the utilization of Micro Hydro Power Plants (MHP) in Karangtengah Village, Banyumas Regency. The background of this research is based on the success of the local community in establishing energy independence through MHP, which later triggered a conflict with Perusahaan Listrik Negara (PLN) as the national electricity provider. This study employs a qualitative approach using literature review and document analysis methods. Data were collected from academic journals, official reports, and relevant media sources, and analyzed using content analysis techniques and the conflict theory perspective of Karl Marx. The results show that the MHP is capable of generating electricity with a capacity of approximately 15 kW and supplying power to dozens to over a hundred households at an affordable tariff. However, this success has led to a conflict of interest between the community and PLN, particularly regarding the control of energy resources, distribution of economic benefits, and authority over the energy system. From a conflict theory perspective, this condition reflects the dynamics of domination and resistance between local actors and state actors. This study concludes that the conflict surrounding MHP is not merely technical but represents a structural conflict in community-based energy management.